Pelargonium radula as a plant bioindicator in monitoring mercury in drinking water - A Majid, Noraishah; Ramli, Nur Syazila; Phang, Ing Chia (Universiti Teknologi Malaysia, 2015)
Pollution by organic and inorganic toxic substances has raised public and environmental concern globally since last decade. However, due to rapid growth of world population along with excessive industrial development, this situation worsens. One of the non-essential heavy metals, mercury (Hg), is a widespread toxic pollutant commonly found in drinking water sources. Therefore, there is a need to monitor the level of Hg in the drinking water. Biomonitoring, which use biological response to assess environmental changes, is one of the approaches that are getting more attention recently. Plant bioindicator offers huge advantages over conventional water quality analysis. Other than cheap, easy to apply and give rapid results; most importantly, people in the rural area can apply this method to monitor water quality without the need of modern equipment and technical expertise. In this study, young leaves from terrestrial plants were treated with water containing Hg solutions. Plant that showed visible morphological changes was selected as potential bioindicator and further analyzed. Over 60 plants were screened including herbs, shrubs and flowering plants. At the 24th h of observation, 15 plants showed morphological changes with several obvious symptoms, including the presence of dark spot, chlorosis, browning of leaves and wrinkle. Among these plants, Plectranthus amboinicus, Lantana camara and Pelargonium radula treated with Hg solutions exhibited morphological changes at the 6th h of treatment, compared to the control. In the present study, Pelargonium radula was chosen as the Hg bioindicator as it gave the fastest and visible morphological changes, which is within 4 h of treatment. This new finding was promising, as it demonstrated that plants could be used for Hg biomonitoring for the safety of drinking water.